Investment Decisions, Funding Decisions, Dividend Policy and Their Effect on The Value of Food and Beverage Companies on The Indonesia Stock Exchange - Harlina Meidiaswati (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
Firm value is very important for managers and investors. To increase the value of the firm, managers are required to be able to make the right financial decisions, which include investment decisions, funding decisions, and dividend policies. The purpose of this study is to analyze the effect of investment decisions, funding decisions, and dividend policy on firm value in food and beverage companies listed in the Indonesia Stock Exchange period 2017-2020. The sample used in this study were 12 companies. The sampling technique used was purposive sampling method. The analysis technique used is multiple linear regression. The results of this study indicate that simultaneously investment decisions, funding decisions, and dividend policy affect firm value. But partially, investment decisions have negative insignificant effect on firm value, funding decisions have positive significant effect on firm value, and dividend policy has positive significant effect on firm value.